Restaurant Green Accounting Policy to Support Sustainable Tourism In Samosir District, Lake Toba - Kemal, Lainatusshifa; Purba, Asra Idriyansyah; Rahma, Annisa Alifa (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to analyze the restaurant green accounting policy in restaurants in Samosir Regency, Lake Toba, in supporting sustainable tourism. Green accounting plays an important role in recording and reporting environmental aspects in the restaurant business, which is an integral part of the tourism ecosystem. This study examines the influence of Corporate Social Responsibility (CSR), management support, and community support on the implementation of green accounting in these restaurants. Using a mix method approach (qualitative and quantitative), data were collected from 71 restaurants in the area. The results showed that CSR, management support, and community support have a significant influence on the implementation of green accounting , which ultimately supports sustainable tourism in Samosir Regency. This study provides important insights for restaurant business actors and stakeholders in designing environmentally friendly and sustainable tourism policies.